Psychosocial Burden of Childhood Sickle Cell Disease on Caregivers in Kenya. (6th May 2020) - Kuerten, Bethany G; Brotkin, Samuel; Bonner, Melanie J; Ayuku, David O; Njuguna, Festus; Taylor, Steve M; Puffer, Eve S
Abstract: Objectives: To characterize the types and magnitude of psychosocial burden present in caregivers who have a child with sickle cell disease (SCD) in Kenya and to identify predictors of caregiver psychosocial burden, including disease severity and financial hardship. Methods: Primary caregivers ( N  = 103) of children aged 1–10 years diagnosed with SCD completed surveys assessing multiple domains of caregiver quality of life (QOL), adjustment to child illness, mental health, and financial hardship. Descriptive statistics characterize psychosocial burden, and linear models assess associations. Results: On indicators of QOL, caregivers report multiple difficulties across most domains, including daily activities and physical, social, cognitive, and emotional well-being. Daily activities emerged as most burdensome. On indicators of parental adjustment to chronic illness, guilt and worry emerged as the greatest concern, followed by long-term uncertainty and unresolved sorrow and anger; relative to these, they reported higher levels of emotional resources. Financial hardship was high, as caregivers reported moderate to major financial losses due to the time spent caring for their child. General linear model analyses revealed that level of financial hardship was a significant predictor of all negative psychosocial outcomes. Conclusions: Results document that Kenyan caregivers of children with SCD experience difficulties across multiple domains of functioning and that financial difficulties are likely associated with psychosocial burden. Results can guide intervention development for caregivers of children with SCD in low-resource, global contexts.